Upaya Penanggulangan Terhadap Anggota Kepolisian Yang Terlibat Tindak Pidana Peredaran Narkotika (Studi Kasus Di Kepolisian Resort Kota Besar Medan) - Boby Hartawan (Universitas Islam Sumatera Utara, 2020)
Police officers who are supposed to be law enforcers commit acts that are contrary to the law for the benefit of the narcotics business.The problem in this thesis is how the factors underlying the occurrence of criminal acts of narcotics distribution by members of the police in Medan City Resort Police, how is the role of Medan City Resort Police in tackling narcotics abuse by the police in Medan City Resort Police, how can effort be made in overcoming criminal acts of narcotics distribution by unscrupulous members of the police and obstacles encountered in Medan City Resort Police.This research uses a descriptive method through an empirical juridical approach that is an approach to the problem, conducted by doing interviews by connecting with various aspects of law in terms of applicable regulation.The results showed that the role of Medan City Resort Police was to carry out law enforcement against individual members of Medan City Resort Police who had been proven to have committed a crime, especially narcotics through general courts.In addition to the general court of law for members of the police who commit crimes there will also be another addition, namely from the internal police itself in the form of law enforcement through the trial of the police code of ethics.Factors underlying the occurrence of criminal acts narcotics distribution by unscrupulous members of the police in Medan City Resort Police are mental, economic, and environmental factors. Economic factors are the dominant factors that cause impetus to commit drug trafficking crimes because by trafficking narcotics the result can be directly used to meet the needs of daily life. Efforts that can be made in tackling the crime of narcoticsdistribution by unscrupulous members of the police and the obstacle faced in Medan City Resort Police is to make efforts to overcome the Non Penal through pre-emptive, preventive efforts. This effort was made to prevent narcotics trafficking through direct control and supervision with the aim that the potential for crime would not develop into a factual threat. Another effort is to carry out legal proceedings if the police carry out criminal acts of narcotics abuse and distribution.Key-Words: Prevention, Circulation, Narcotics.